Industrial training report: Maryam Khadijah(MK) / Nur Qamarina Husna Abdullah - Abdullah, Nur Qamarina Husna (Universiti Teknologi MARA, Perlis, 2023)
Maryam Khadijah (MK) is a brand of scarves company that provides a variety of wides scarves for Muslim career women. 70% of business operations are online. Most of its customers are Singapore buyers. MK has a good brand name and image but has yet to be widely known in the Malaysian market. The company is known for its product and packaging quality, various payment methods, fast complaint response and loyal customers. But Maryam Khadijah also has a problem with a high rate of return employees, does not have proper inventory control, a branding strategy is not recognized in the local market and does not have suitable equipment for marketing activity. Therefore, Maryam Khadijah needs help competing in an intense competition with its competitor and needs a good strategy to overcome the economic situation, such as inflation which can affect the business activity. Next is something that MK cannot control, which is the currency problem and Changing in social media and search algorithms. Lastly, even though the company has difficulty operating its business, there are also opportunities. Such as entering the international market, using Metaverse in digital marketing, collaborating with a big company, installing payment such as SpayLater and expanding the target market to younger career women.